Surveying the Impacts of COVID-19 on the Perceived Productivity of Brazilian Software Developers - Oliveira, Edson; Leal, Gislaine; Valente, Marco Túlio; Morandini, Marcelo; Prikladnicki, Rafael; Pompermaier, Leandro; Chanin, Rafael; Caldeira, Clara; Machado, Letícia; Souza, Cleidson de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
The new coronavirus pandemic has forced companies around the world to adopt measures to stop the spread of this virus and the associated COVID-19 disease. In Brazil, this was no different with software development professionals having to work from home (WFH) due to the need of social isolation. WFH was an imposition and was a new experience for many professionals, generating unpredictable impacts. In this article, we present the results of a survey to understand the impacts of social isolation on the perceived productivity of Brazilian software developers. Data were collected during March and April/2020 with a sample of 413 respondents. The results indicate developers' perceived productivity has increased, mainly because there are fewer interruptions throughout the day. In addition, most respondents informed that they wish to continue working most of the time remotely. We contrast our results with another study published on this topic.